2016
DOI: 10.1039/c6ja00251j
|View full text |Cite
|
Sign up to set email alerts
|

Compositional depth profiling of diamond-like carbon layers by glow discharge optical emission spectroscopy

Abstract: This article describes the compositional depth profiling (CDP) of diamond-like carbon (DLC) layers by Glow Discharge-Optical Emission Spectrometry (GD-OES).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…These features include diamond crystals, exsolved clusters of SiC crystallites, and embedded particulates (probably either common dust and/or silicon powder present from cleaving wafers in the lab). Raman spectroscopy gave results consistent with inferred variations in composition (e.g., the presence/absence of silicon or silicon carbide domains) and bonding (e.g., variable ratios and distributions of sp 3 vs. sp 2 carbon bonds) among analysed areas. SIMS analysis conrmed a non-uniform distribution of minor siliconlikely inherited from the sputtering target used for the fabricationand the presence of occasional embedded particulates.…”
Section: Sources and Examples Of Observed Matrix Effects In Dlcsupporting
confidence: 69%
See 2 more Smart Citations
“…These features include diamond crystals, exsolved clusters of SiC crystallites, and embedded particulates (probably either common dust and/or silicon powder present from cleaving wafers in the lab). Raman spectroscopy gave results consistent with inferred variations in composition (e.g., the presence/absence of silicon or silicon carbide domains) and bonding (e.g., variable ratios and distributions of sp 3 vs. sp 2 carbon bonds) among analysed areas. SIMS analysis conrmed a non-uniform distribution of minor siliconlikely inherited from the sputtering target used for the fabricationand the presence of occasional embedded particulates.…”
Section: Sources and Examples Of Observed Matrix Effects In Dlcsupporting
confidence: 69%
“…In addition, there are strong variations in ion yields; we surmise that these variations are a function of an inconsistent electrical conductivity on the sample. This inference is based in part on the work by Sullivan et al (1998), 12 who showed that 2.5 mm 2 columns of DLC can vary in conductivity by more than 10Â as the concentration of sp 3 bonds and the relative size, orientation and connectivity of their domains vary with respect to the sp 2 domains within the DLC. Assuming that these variations exist in our similar DLC, the effect of these domains on SIMS analyses can be imagined as analogous to analysing a wafer which has a matrix of an electrically conducting material that contains $70% by volume embedded, unevenly distributed, micron-sized particles of an insulator.…”
Section: Sources and Examples Of Observed Matrix Effects In Dlcmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration curve is a basis for the quantification. If a sample with the known concentration and sputtering rate deviates from the calibration curve, the quantification of concentration and thickness will be wrong [33]. The calibration curve of hydrogen is represented in Figure 4b.…”
Section: Calibration Of Gd-oes With the Use Of Zr-25nb Samplesmentioning
confidence: 99%
“…However, in analytical applications, empirical functions are used, established by the calibration, and are represented by a higher-order polynomial instead of the direct proportionality [33]. In this case, a two-order polynomial function was used in the calibration of zirconium (Figure 3a).…”
Section: Calibration Of Gd-oes With the Use Of Zr-25nb Samplesmentioning
confidence: 99%